Pola sebaran kupu-kupu pada berbagai tipe ekosistem di Gunung Ciremai - Noerdjito, Woro A.; Erniwati, Erniwati (JURNAL BIOLOGI INDONESIA, 2009)
ABSTRACTDistribution Pattern of Butterflies on Various Ecosystem at Mt. Ciremai. To know the effectof ecosystem type on distribution pattern of butterflies in Ciremai mountain, we comparedbutterfly fauna between urban area (perkampungan), secondary and primary forest from 1000m asl to 1700 m asl., located in Apuy and Linggarjati tracks. During our study in Apuy (4 â 22April 2006) and Linggarjati (15 Mayâ 4 June 2007) we recognized 66 species within 7 groups.Four groups distributed in specific habitats such as (1) perkampungan (Argomukti vilage,Apuy, 1000-1200 m.asl.), (2) secondary forest (Legok Pasang, Apuy, 1500-1600 m.asl.), (3)outsite forest Linggarjati, 800-1100 m.asl. (4) Linggarjati forest edge at 1100-1400 m asl. Theothers groups are butterflies that only distributed in Linggarjati or Apuy. Microclimate duringour study as well as weather condition at the time such as cloud, wind and rain impact theactivity of butterfly species and reflected to the species collected. Although the researchconducted in the same season (wet season) but Apuy and Linggarjati have differentmicrohabitats that caused some species are only found at Apuy or Linggarjati areas.Key words: Ciremai, butterfly, distribution